Evaluation of Antidiabetic, Antioxidant and Other Phytochemical Properties of Thai Fruits, Vegetables and Some Local Food Plants - Suree NANASOMBAT; Kanokwan YANSODTHEE; Ilada JONGJAITED (My University, 2019)
Antidiabetic, antioxidant, anti-acetylcholinesterase and prebiotic activities, total phenolics and flavonoids of 33 crude ethanolic extracts of Thai local fruits, vegetables and some local food plants were determined. Mangosteen (Garcinia mangostana) fruit peel and Indian gooseberry (Phyllanthus emblica) fruit extracts had highest antioxidant activity. Bamboo grass (Tiliacora triandra) leaf extract had strongest α-amylase inhibitory activity (78.28 % inhibition), while mulberry (Morus alba) fruit extract had strongest α-glucosidase inhibitory activity (59.63 % inhibition). Star cactus (Aloe vera) leaf pulp extract had strongest anti-acetylcholinesteraseVactivity (31.55 % inhibition). Indian gooseberry fruit and mangosteen fruit peel extracts had highest content of total phenolics and flavonoids, respectively. The extract with highest indigestible polysaccharide content was the extract of mangosteen fruit peels (188.62 mg/g extract), while those with relatively high indigestible polysaccharides were the extracts of pineapple fruits (Ananas comosus), lotus seeds (Nelumbo nucifera), black rice grains (Oryza sativa) and pisang mas banana fruits (Musa sapientum). Based on these properties, 5 plant extracts were selected to study for their prebiotic effect on growth and fermentation of Lactobacillus acidophilus, Lactobacillus bulgaricus and Streptococcus thermophilus in yogurt at 42 °C. Addition of lotus seed extract resulted in highest proliferation of these bacteria with 2.24 logCFU/g increase of total lactic acid bacterial counts in yogurt after 24 h fermentation, while addition of black rice grain, pisang mas banana fruit and pineapple fruit extracts caused good growth of these bacteria with 2.12 - 2.19 logCFU/g increase of total counts.
Keywords: Garcinia Mangostana; Ananas; Natural Antidiabetic Agents Studies